Write2Gether talk series: AI tools for efficient academic writing / Dr. Aisyah Hasyila Jahidin and Associate Prof. Dr. Mahmathi Karuppannan - Jahidin, Aisyah Hasyila; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Write2Gether is one of the projects under the strategic initiative PROLIFIC, which is an acronym for PROmoting impactful pubLIcation From academICs. The general objective of PROLIFIC is to enhance the publication output of faculty members by focusing on high-quality journals that have a significant impact on the community. To accomplish this objective, a series of talks and workshops have been scheduled, including a virtual talk on artificial intelligence (AI) tools which took place on the 24th of May 2023.